What Do We Know About the Chevrel Technique in Ventral Incisional Hernia Repair? - Köckerling, Ferdinand (Frontiers in Surgery, 2019)
Introduction In publications on ventral incisional hernia repair the Chevrel technique and the onlay operation are often equated. This present review now aims to present the difference between these surgical techniques and analyze the findings available on the Chevrel technique. Material and Methods A systematic search of the available literature was performed in January 2019 using Medline, PubMed, Scopus, Embase, Springer Link, and the Cochrane Library, as well as a search of relevant journals, books and reference lists. Thirty-four publications were identified as relevant for this review.For assessement of the Chevrel-technique with other surgical procedures no randomized controlled trial, prospective or retrospective comparative study but only case series are available. In the majority of case series the follow-up procedure is not reported. Results Whereas in the onlay technique the defect is closed with direct suture or this is omitted, in the Chevrel technique this is done with sliding myofascial flaps harvested from the rectus sheaths. In the few case series available this appears to result in a lower recurrence rate for the Chevrel technique compared with the onlay technique. However, the rates of postoperative complications, surgical site occurrences (SSOs), surgical site infections (SSIs), seroma and skin necrosis are as high as in the onlay technique. The reason for that is that both techniques require subcutaneous undermining with severance of perforator vessels. Conclusion If mesh placement in onlay position has been chosen for specific reasons, preference can be given to the Chevrel technique over the standard onlay technique, although the study quality is limited. Conclusion If mesh placement in onlay position has been chosen for specific reasons, preference should be given to the Chevrel technique over the standard onlay technique.